Kebijakan Perlindungan Pekerja Migran Perempuan Kabupaten Blitar - Ikmal, Novita Maulida; Holifah, Nur; Indriastuti, Indriastuti; Prabowo, Veny (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
This study aims to analyze the strategies and challenges in implementing gender-responsive protection policies for Indonesian migrant workers. Migrant worker protection is a strategic issue that requires attention to gender equality, given that the majority of migrant workers are women and are vulnerable to discrimination, violence, and exploitation. This study uses a qualitative descriptive approach, collecting data through in-depth interviews, observations, and reviewing policy documents at the central and regional levels, particularly at the One-Stop Integrated Service (LTSA). The results indicate that the main strategies for policy implementation include strengthening institutional capacity, providing gender-based services, improving legal literacy for migrant workers, and strengthening inter-agency cooperation. However, implementation still faces various challenges, including limited human resources with a gender perspective, suboptimal cross-sectoral coordination, and minimal policy dissemination at the grassroots level. This study recommends the need to integrate a gender perspective into every stage of migrant worker protection, increase gender-responsive budgets, and involve civil society in policy oversight.